Adversities faced by Y or Z category health science journals with HEC, Pakistan - Naima Fazil Raja , Asmat Perveen , Imran Mahmood Khan Maqbool Hussain , Jai Krishin , Sajid Hussain Sherazi, Naima Fazil Raja , Asmat Perveen , Imran Mahmood Khan Maqbool Hussain , Jai Krishin , Sajid Hussain Sherazi (Journal of Rawalpindi Medical College, 2020)
Objective: To know the rate and predictors for derecognition/demotion in HEC-indexed Y, and Z categories health science journals (HSJs) Methods: A list of HEC-indexed Y and Z categories HSJs was downloaded from the official website of HEC, Pakistan on 29 July 2019. General information like the type of publisher, specialty, sponsoring body, origin city, and sector (Armed Forces/Civilian) of the derecognized or demoted journals were noted. Fundamental issues like HEC's procedures were resolved using literature review, contacts to the affected journals, and peer-to-peer discussions. Results: Of 50 journals, 25 (50%) were found against each of the Y and Z categories. Fourteen (56% of the total) Y category journals faced adversity in the form of derecognition (n = 5) or demotion (n = 9). Whereas, the rate increased remarkably to 64% (n = 16) in the Z category. Similarly, the high rate was noticed in specialty-specific journals (67.9%, n =19). A journal under private sponsorship had twofold more chance of the adversity (95%CI:1.003-2.918, p = .05) than public-sponsored journals (75 vs. 50%, respectively). Most of the affected Z category journals (n = 13, 81.3%) had their first registration with HEC before 2015. Conclusion: The policy of HEC for derecognition/demotion of HSJs needs extensive review to promote medical publications.